2020
DOI: 10.3389/fnagi.2020.554660
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Network Associated With Cognitive Performance in Early Parkinson Disease Measured by Eigenvector Centrality Mapping

Abstract: Objective: To investigate relationships between whole-brain functional changes and the performance of multiple cognitive functions in early Parkinson's disease (PD). Methods: In the current study, we evaluated resting-state functional MRI (rsfMRI) data and neuropsychological assessments for various cognitive functions in a cohort with 84 early PD patients from the Parkinson's Progression Markers Initiative (PPMI). Eigenvector centrality (EC) mapping based on rsfMRI was used to identify the functional connectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The chosen eigenvector centrality mapping (ECM) approach allows for assumption‐free analysis of functional network connectivity (Chase et al, 2020 ; Meinzer et al, 2015 ). Graph theoretical approaches have previously been reported to detect network correlates of cognitive functions in health and disease, and modulations of these functions induced by transcranial electrical stimulation (Antonenko, Nierhaus, Meinzer, et al, 2018 ; Arnemann et al, 2015 ; Binnewijzend et al, 2014 ; Cao et al, 2020 ; Gundlach et al, 2020 ; Lou et al, 2015 ; Meinzer et al, 2012 ; Meinzer et al, 2013 ; Schoonheim et al, 2014 ; Sehm et al, 2012 ). Interestingly, tDCS‐induced increase as well as decrease in network centrality has previously been associated with improved behavioral performance (Meinzer et al, 2012 ; Meinzer et al, 2015 ; Sehm et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The chosen eigenvector centrality mapping (ECM) approach allows for assumption‐free analysis of functional network connectivity (Chase et al, 2020 ; Meinzer et al, 2015 ). Graph theoretical approaches have previously been reported to detect network correlates of cognitive functions in health and disease, and modulations of these functions induced by transcranial electrical stimulation (Antonenko, Nierhaus, Meinzer, et al, 2018 ; Arnemann et al, 2015 ; Binnewijzend et al, 2014 ; Cao et al, 2020 ; Gundlach et al, 2020 ; Lou et al, 2015 ; Meinzer et al, 2012 ; Meinzer et al, 2013 ; Schoonheim et al, 2014 ; Sehm et al, 2012 ). Interestingly, tDCS‐induced increase as well as decrease in network centrality has previously been associated with improved behavioral performance (Meinzer et al, 2012 ; Meinzer et al, 2015 ; Sehm et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the traditional concept -frontal region to be the primary cortical substrate for working memory and executive function-related tasks -supports our findings. A previous study [69] on the whole brain of early Parkinson's patients observed verbal memory positively correlating with functional connectivity of SFG. In addition, Hou et al [70] demonstrated that functional connectivity between the inferior parietal and bilateral superior frontal gyrus is associated with improved memory function in drugnaïve PD patients.…”
Section: Network Analysismentioning
confidence: 72%
“…Also, Left Inferior Temporal Gyrus of the mentioned network was found using local e ciency and Betweenness centrality with KMI. Cao et al(Cao et al 2020) also found that eigenvector centrality of the superior frontal gyrus correlated signi cantly with neuropsychological scores. We also found this region to be signi cant using page rank centrality and degree only with KMI as well as Betweenness centrality with both KMI and MI.Hall et al(Hall et al 2018) found Thalamus contributes to Parkinson's disease in participation coe cient, which is in line with our results.…”
mentioning
confidence: 89%